Incidence of Surgical Site Infection in Patients Presented for Orthopaedic Surgery - Muhammad Bilal, Asifa Karamat, Muhammad Shakeel Basit, Muhammad Saleem Bashir, Qasim Naqvi, Gull Mahnoor Hashmi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the incidence of surgical site infection in clean cases of orthopaedic surgery. Study design: Retrospective descriptive study. Setting: Trauma and orthopaedic unit Gulab Devi Hospital. Duration: April 2018 to November 2021 Methodology: Using non probability (purposive) sampling a total of 800 patients who underwent an invasive surgical procedure during the specified time period was included in the study. While all non-invasive procedures such as manipulations, application of plaster casts and image guided intra-articular injections were excluded from study. p-value< 0.05 was considered as significant Results: There were 504(63%) male patients and 296(37%) female patients. Age range was between 01 to 86 years. Mean age was 30±6.7 years. After performing surgery, all patients were followed up for minimum of four weeks to record SSIs. Post-operatively infection was detected in 17(2.12%) of our patients. SSI was 5.8% in clean cases, 23.5% in clean contaminated and 70.5% in dirty cases. The prevalence of SSI were significantly higher in those patients already having dirty wound before procedure as p<0.05 Conclusion: Surgical Site infection (SSI) rates reported in this study setting are are comparable to international standards. Keywords: Orthopedic, Surgical site infections, Trauma, Wound management